Evaluation of the clinical-radiographic results of patients undergoing arthroscopic metatarsal-phalangeal arthrodesis of the hallux - Gomes, Rogério de Andrade; Jannotti Pádua, Bruno; Humberto Gomes, Anderson; Brandão Magalhães, João Murilo; Vieira da Fonseca, Wagner; Galo Magalhães, Tauam Filipe; Moreira Teixeira, Luiz Eduardo (Journal of the Foot & Ankle, 2021)
Introduction: Hallux rigidus (HR) is a frequent pathological condition of the foot, responsible for marked functional impairment. Metatarsal-phalangeal arthrodesis is an excellent treatment alternative for advanced stages of the disease, usually performed as an open surgery. Forefoot arthroscopy had its greatest development in the last decade, with a progressive expansion of indications, yielding encouraging results. Objective: To present the clinical and radiographic results of patients undergoing arthroscopic metatarsal-phalangeal arthrodesis of the hallux, depicting the technique and reporting complications. Methods: This study involves a series of cases, we operated 9 patients (10 feet), all with advanced HR (grades 3 and 4 - Coughlin-Shurnas). The patients underwent an arthroscopic procedure through two dorsal portals, small joints instruments. We assessed the results using the AOFAS functional score and the visual analogue pain scale. The radiographic parameters we used to analyze were the metatarsal-phalangeal angulation in the anteroposterior (pre- and postoperative) and lateral (post-operative) views, and we measured the radius shortening. Conclusion: Arthroscopic metatarsal-phalangeal arthrodesis is an excellent treatment option in advanced stages of hallux rigidus, with minimal disruption and providing excellent results, in addition to a low incidence of complications. Level of Evidence IV; Therapeutic Studies; Case Series